Feasibility study on underground storm water storage - Ho, Hong Whatt. (2008)
Singapore is a small island republic of only 633 km2 in area. Two of its major constraints are the shortage of land and of water supply. The objectives of this dissertation are to explore the feasibility of constructing underground rock cavern in the Bukit Timah granite which covers nearly one third of the island and utilising the space created by these rock cavern for storing storm water.